1989
DOI: 10.1152/ajpheart.1989.256.2.h598
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of regional responses to endothelin in hindquarters vascular bed of cats

Abstract: Regional responses to endothelin, a peptide derived from endothelial cells in culture, were investigated in the hindquarters vascular bed of cats, when flow varied naturally and when flow was maintained constant with a pump. Intravenous injections of endothelin at doses of 0.03 and 0.1 nmol/kg caused dose-dependent decreases in systemic arterial pressure and increases in distal aortic blood flow. Injection of endothelin at a dose of 0.3 nmol/kg iv caused a biphasic response characterized by an initial decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…It has been reported that an intravenous bolus injection of ET results in an early transient depressor response followed by a sustained pressor response in anesthetized animals (Inoue et al 1989;Minkes et al 1989), and that selective ETA receptor antagonists attenuate only the pressor effect of ET Miyata et al 1992). In rat isolated perfused mesentery, ET-1 was several times more potent than ET-3 in inducing vasoconstriction, whereas ET-3 was more potent than ET-1 in inducing a vasodilation response in these vessels (Minkes et al 1989;Warner et al 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that an intravenous bolus injection of ET results in an early transient depressor response followed by a sustained pressor response in anesthetized animals (Inoue et al 1989;Minkes et al 1989), and that selective ETA receptor antagonists attenuate only the pressor effect of ET Miyata et al 1992). In rat isolated perfused mesentery, ET-1 was several times more potent than ET-3 in inducing vasoconstriction, whereas ET-3 was more potent than ET-1 in inducing a vasodilation response in these vessels (Minkes et al 1989;Warner et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that an intravenous bolus injection of ET results in an early transient depressor response followed by a sustained pressor response in anesthetized animals (Inoue et al 1989;Minkes et al 1989), and that selective ETA receptor antagonists attenuate only the pressor effect of ET Miyata et al 1992). In rat isolated perfused mesentery, ET-1 was several times more potent than ET-3 in inducing vasoconstriction, whereas ET-3 was more potent than ET-1 in inducing a vasodilation response in these vessels (Minkes et al 1989;Warner et al 1989). The ET-3 induced vasodilation is considered to be mediated through activation of ETB receptors with subsequent release of vasodilator substances such as endotheliumderived relaxing factor (EDRF), nitric oxide (NO), or prostacyclins from the endothelium (de Nucci et al 1988;Warner et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Human big ET (human ET ) and a common carboxy terminal fragment of ET (ET [17][18][19][20][21]) were synthesized by the solid phase method. 6 …”
Section: Peptidementioning
confidence: 99%
“…Yanagisawa et al (1) found that ET con stricted rat aortic strips in a dose-dependent manner, where the initial dose for constriction was 10-" M and the EC50 was 5 6 X 10' M. However, it has been reported that in travenous bolus injection of ET (0.1 to 3 nM/kg) causes a transient, dose-related de pressor response (2,3). Even in in vitro ex periments, vasodilating effects of ET, particu larly at low doses, have been demonstrated (4)(5)(6).…”
mentioning
confidence: 99%